A new more atom-efficient multi-component approach to tetrasubstituted imidazoles: one-pot condensation of nitriles, amines and benzoin. Issue 71 (15th July 2016) - Khalafi-Nezhad, Ali; Shekouhy, Mohsen; Sharghi, Hashem; Aboonajmi, Jasem; Zare, Abdolkarim
Abstract : A new more atom-efficient multi-component approach for the synthesis of tetrasubstituted imidazoles via the one-pot condensation of nitriles, primary amines and benzoin has been described. Abstract : A new more atom-efficient multi-component approach for the synthesis of tetrasubstituted imidazoles via the one-pot condensation of nitriles, primary amines and benzoin has been described. Using this method, a wide range of structurally diverse nitriles and primary amines were successfully condensed with benzoin in glycerol in the presence of TFA under microwave irradiation at 120 °C and all the products were obtained in good to excellent yields with higher atom efficiencies in comparison with the commonly used four-component condensation of aldehydes, ammonium acetate, primary amines and benzil.